Physical Performance Trajectories and Mortality Among Older Mexican Americans. (9th February 2018) - Mutambudzi, Miriam; Chen, Nai-Wei; Howrey, Bret; Garcia, Marc A; Markides, Kyriakos S
Abstract: Background: We sought to identify distinct trajectory classes of physical performance in Mexican Americans aged 75 years and older and to examine whether these trajectories predict mortality. Methods: We used four waves of Hispanic Established Populations for Epidemiologic Studies of the Elderly (H-EPESE) data for adults 75 years and older from 2004–2005 to 2013. Latent growth curve analysis was used to identify distinct trajectory classes. Multinomial logistic regression analysis was used to examine the association between baseline characteristics and the newly constructed trajectories. Cox proportional hazards regression models examined the hazard of mortality as a function of Short Physical Performance Battery (SPPB) trajectories. Results: The study follow-up period was approximately 9.5 years. One thousand four hundred and eleven adults were successfully classified into three (low-declining, high-declining, and high-stable) physical performance trajectory classes. Depressive symptoms (relative risk ratio = 1.94, 95% confidence interval [CI] = 1.17–3.22), diabetes (relative risk ratio = 2.44, 95% CI = 1.63–3.65), number of other comorbid health conditions (relative risk ratio = 1.40, 95% CI = 1.16–1.68), and obesity (relative risk ratio = 2.83, 95% CI = 1.67–4.80), increased the relative risk of classification into the low, relative to high-stable trajectory class. Male gender and foreign-born status significantly reduced risk of classification in the low-declining and high-declining trajectory classes. We observed a statistically significant association between low-declining (hazard ratio = 3.01, 95% CI = 2.34–3. 87) and high-declining (hazard ratio = 1.64, 95% CI = 1.32–2.03) trajectories and increased risk of mortality. Conclusions: Differences in mortality across physical performance trajectory classes suggest that these physical performance classes represent differences in underlying disease progression, and thus differences in mortality risk among older Mexican Americans, which warrants additional research to better understand differential physical performance trajectories and their effects on morbidity and mortality in heterogeneous aging populations.